Compound eye as a target organ of white spot baculovirus (WSBV) in Penaeus indicus H. Milne Edwards - Jose, Jasmine K; Manissery, Mary K (Indian Journal of Fisheries, 2011)
Recently mass mortalities of penaeid prawns have been reported worldwide inthe culture ponds due to the occurrence of White Spot Disease (WSD). Eventhough,several tissues of ectodermal and mesodermal origin have been confirmed to bethe target organs for white spot baculovirus, not much importance has been givenso far to the compound eyes of penaeid prawns affected with WSD. Histopathologicaland ultrastructural studies were conducted in the compound eye ofPenaeus indicus H. Milne Edwards, affected with WSD. Eosinophilic tobasophilic intranuclear inclusion bodies were observed in the narrow region ofthe retinular cell nuclei in the dioptic portion of the ommatidia. Electronmicroscopic examination of the compound eye revealed the presence of rodshaped,enveloped, non-occluded virions and viral particles in the affected nucleiof retinular cells.